Nanoporous multimetallic Ir alloys as efficient and stable electrocatalysts for acidic oxygen evolution reactions - Chatterjee, Swarnendu; Intikhab, Saad; Profitt, Lauren; Li, Yawei; Natu, Varun; Gawas, Ramchandra; Snyder, Joshua (Journal of catalysis, 2021)
[Display omitted] •Electrolyte additives drive the propagation of etch fronts in high melting alloys during dealloying.•Free standing np-Ir electrodes exhibit a significant enhancement in OER activity and stability.•HCD performance is a consequence of reduced electrode resistivity for np-Ir. The dearth of appropriate electrocatalysts for stable anodic water splitting, oxygen evolution reaction (OER), in acid has given rise to concerted efforts toward making iridium-based high aspect ratio nanomaterials, as iridium and its higher valent oxides have been shown time and again to exhibit the most optimal balance between activity and durability. Here, we show a dealloying strategy to synthesize free-standing 3D, oxide skinned nanoporous Ir electrocatalysts (np-Ir) with demonstrated enhanced activity and durability in comparison to more traditional IrOx nanoparticulate catalysts. The metallic core and absence of any binder/support result in low electrode and charge transfer resistance, ultimately giving rise to lower OER overpotentials and improved activity.